2016
DOI: 10.3892/mco.2016.899
|View full text |Cite
|
Sign up to set email alerts
|

Differences in displacement of the proximal and distal ends of mid-upper thoracic esophageal squamous cell carcinoma

Abstract: Abstract. In the present study, clips were used as markers to evaluate displacement differences between proximal and distal ends of esophageal tumors and to test whether their internal target volume (ITV) margins should be determined separately. A total of 23 patients with mid-upper thoracic esophageal squamous-cell carcinoma, a tumor length of ≤8 cm and an esophageal lumen suitable for endoscopic ultrasonography were recruited for the present study. Clips were implanted endoscopically at the proximal and dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Previous studies indicated that the esophageal tumor motion is variable according to several factors such as the region of the esophagus or the direction of motion. 10 , 11 , 12 , 13 , 14 , 15 , 16 In addition to these factors, our present findings revealed that cT stage also influenced the esophageal motion and the ITV margin in esophageal cancer. If the patient-specific ITV is to be used, the ITV margin should be determined using the several 4D phase images of each patient.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Previous studies indicated that the esophageal tumor motion is variable according to several factors such as the region of the esophagus or the direction of motion. 10 , 11 , 12 , 13 , 14 , 15 , 16 In addition to these factors, our present findings revealed that cT stage also influenced the esophageal motion and the ITV margin in esophageal cancer. If the patient-specific ITV is to be used, the ITV margin should be determined using the several 4D phase images of each patient.…”
Section: Discussionsupporting
confidence: 61%
“…Several studies reported the ITV margins for primary esophageal tumor. Qiu et al 15 evaluated the displacement differences of markers between proximal and distal ends of tumor and investigated whether the ITV margins should be determined separately in patients with mid-upper thoracic ESCC. The ITV margins that covered 95% of their datasets in the LR, AP, and SI directions were 2.9, 2.4, and 5.0 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The esophagus is a long tubular organ extending from the neck to the upper abdomen, surrounded by various structures [8,9]. Esophageal tumors tend to grow and migrate longitudinally along the esophageal wall.…”
Section: Introductionmentioning
confidence: 99%